The Translation of the English F-word into Indonesian - Sisiana Dewi, Ni Luh Putu; Rajeg, I Made; Seri Malini, Ni Luh Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
This article aims to analyze the translation strategies applied when translating the word “fuck” in Everything is F*cked into Indonesian’s Segala-galanya Ambyar . By using the descriptive qualitative method supported by the note-taking technique, the data were collected with a linguistic software application of parallel corpus named AntPConc version 1.2.1 (Anthony, 2017). The keyword “*fuck*” is used to create a concordance containing the lexical fuck and its derivation (fuckedness), inflection (fucking), or compound form (clusterfuck). The collected data were analyzed using a theory of translation and translation strategies. The result showed that five translation strategies are applied. They are translation by a more general word (superordinate), a more neutral/less expressive word, cultural substitution, paraphrase using unrelated words, and omission. The translation by a more neutral/less expressive word was the most frequently used strategy.